Injectable, Manganese-Labeled Alginate Hydrogels as a Matrix for Longitudinal and Rapidly Retrievable 3D Cell Culture - Malysz-Cymborska, Izabela; Golubczyk, Dominika; Walczak, Piotr; Stanaszek, Luiza; Janowski, Miroslaw (International journal of molecular sciences, 2025)
Hydrogels are one of the most attractive biomaterials, used in both three-dimensional (3D) and in vivo cultures. They facilitate the reconstruction of tissue microenvironments by preserving the spatial arrangement of cells, cell–cell interactions, and functional dynamics in the tissue. In this work, the long-term effect of alginate hydrogel on cell culture and the possibility of rapid cell recovery by dissolving the hydrogel were investigated. Mouse glial-restricted progenitors (GRPs) and porcine mesenchymal stem cells (MSCs) were suspended in hydrogels; their metabolic activity, viability, and expression of genes, which are involved in oxidative stress, apoptosis, proliferation, migration, and differentiation, were assessed using quantitative polymerase chain reaction (qPCR). The concentration that was able to dissolve the hydrogel and was the least harmful to the cells was 0.005 M ethylenediaminetetraacetic acid (EDTA). The metabolism of both cell types was reduced from the beginning of the experiment to day 3. From day 7 to the end of the experiment, the normalization of the GRP metabolism was observed, in contrast to the MSCs. For the apoptosis-related genes, caspase 3, 7, and B-cell leukemia (Casp3, Casp 7, Bcl2) were increased in GRPs and MSCs on days 0 and 1. After 3 and 7 days, an increase in the expression of oxidative stress genes (nuclear factor of activated T-cells 5—NFAT5 and autophagy-related 14-ATG14) was observed in cells cultured in calcium chloride (CaCl2). GRPs cultured in calcium alginate (CaM) were not affected and, remarkably, showed increased Antigen Kiel 67 (Ki67) levels after 30 days. In conclusion, alginate hydrogels provide an excellent environment for stem cell culture in 3D for a longer period of time, but this is dependent on the cell type. Therefore, an individual approach to cell culture is necessary, taking into account the requirements of the cells to be used.